Parallel computation of finite difference method for heat conduction in duct problem - Abd. Aziz, Noor Syazwana (2012)
This dissertation is about to find a heat conduction in a curvature structure of duct. This problem will be solved using finite difference method and since the heat transfer in curvature is different from straight duct, heat equation must to be transformed into modified polar coordinate. OpenMP parallel was applied in this problem to speed up the calculation and the method used in parallel is Gaussian Elimination. Speedup for each processor will be calculated using formula ?? ?? = ??(1) ??(??) in order to know how fast this problem will be solved after applying the parallel method. The result shows that the temperature was decreasing gradually and became smaller at the end of duct and the graph show that area at inlet is bigger than area at outlet of duct. Obviously, results show that the geometry of shape affect the flow of heat transfer. Time reduction in parallel computation is due to parallel Gauss elimination method as well as parallel file handling technique.